Pendampingan Penggunaan Software SPSS dalam Pengolahan Data Statistik - Sefna Rismen; Ramadoni; Lita Lovia (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Officers' limitations in assessing data in district offices. The majority of these issues are caused by lack of apparatus knowledge and skill, as well as a limited number of computers. The district office's data is not adequately preserved, and there is no data management or technology-assisted data display. Training and mentorship are provided as a way of implementation. The training presented consists of fundamental skills in using SPSS to present district population data. Its operations in the Surau Gadang District include training and support in presenting and processing data using the SPSS application. The service implementation conducted interviews and distributed questionnaires to determine the extent of the training participants' grasp of the use of SPSS software. The service team clearly and concisely explained the data presented. This SPSS program assists district personnel in understanding and analyzing data. It is useful to district officials in their job with the applications taught.